Technology of preventive turnaround of pipelines subject to groove corrosion - Timur S. Sultanmagomedov; Sultanmagomed M. Sultanmgomedov; Khiramagomed Sh. Shamilov; Adeliia R. Urmanova (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2025)
Relevance. The paper proposes a methodology for modeling the technological parameters of preventive turning of a pipeline subject to groove corrosion. Such a turning is performed in order to remove the groove from the zone of intensive corrosion. To perform a preventive turnaround, it is necessary to know the geometric characteristics of the groove, soil properties, depth of the pipeline, corrosion rate, and operating pressure in the pipeline. In order to turn without destroying the pipeline to a given angle, it is necessary to estimate the gripping force, the torque applied to the pipeline and the distance between the gripping devices. The research is aimed at creating a method that will allow for the rapid determination of the distance between gripping devices and the force required to rotate the pipeline to the required angle without the risk of plastic deformation in the pipeline or loss of its strength and stability. Aim. Development of a finite element model of the pipeline for simulation of preventive turning and comparison of simulation results with field experiments. Objects. Underground field pipelines subject to groove corrosion. Methods. Mathematical modeling; finite element modeling in ANSYS software; methods of structural mechanics and soil mechanics; experiment planning, field experimentation. Results. The paper presents a comparison of the results of the field experiment on turning at a given angle with the results of modeling. In the field experiment the 219×5,0 pipeline with a length of 146.4 m was rotated at an angle of 28.77° using two gripping mechanisms. Modeling was carried out in the ANSYS software package, the comparison of modeling and experiment was carried out by the rotation angles in characteristic sections, for the section X=21 m, φexp=23°, φcal=25°; for the section X=60.2 m, φexp=21°, φcal=24°. The stress state in the most dangerous cross-section of the pipeline was also calculated taking into account the edge effect, such point was the section adjacent to the point of gripping by the rotary device.